Design of transverse magnetic field sweeping solenoids for 140 GHz mega‐watt gyrotrons. Issue 14 (13th June 2018) - Zeng, Xu; Liu, Bentian; Feng, Jinjun
Abstract : As the overlarge power density at the collector of mega‐watt (MW) gyrotrons limits the increase in their average output power and pulse width, transverse magnetic field sweeping solenoids (TMFSS) with periodical changing magnetic field have been designed for a 140 GHz MW gyrotron developed and tested at Beijing Vacuum Electronics Research Institute. The analysis of the electron trajectories in the collector and the simulation results indicate that the power density could be decreased significantly by applying the solenoids, which will effectively ensure the stable operation of the tube. Meanwhile, different structures of the TMFSS were studied and compared, with the optimised one being used in the future gyrotron assembly and hot testing.